Stomata characters of sugarcane (Saccharum officinarum L.) mutants of GMP3 variety at PT Gunung Madu Plantations, Lampung, Indonesia - Mahfut, Mahfut; Kendari, Putri; Syarif, Admi; Wahyuningsih, Sri; Susiyanti, Endah (Universitas Gadjah Mada, 2023)
The induction of colchicine mutations is one method of breeding. PT Gunung Madu Plantations, for example, has induced mutations of commercial sugarcane (Saccharum officinarum L.) varieties, however, investigations on the impact of colchicine on stomatal characters have received less attention. Therefore, this study aimed to analyse the stomata character of 21 sugarcane mutants of the GMP3 variety at PT Gunung Madu Plantations, Lampung, Indonesia with a focused look at stomata aperture width, stomata length and width, number of stomata, stomatal density, and stomata index. The collected data were analysed using cluster and Principal Component Analysis (PCA) through MVSP software. This study showed that all GMP3 mutants had Graminae-type stomata. In terms of stomata length and width, the average size of the GMP3 variety mutant was greater than that of the control. The diversity of stomata characters is fairly high due to differences in stomata size between GMP3 and control mutants. With a similarity index of 0.20, the phenetic analysis of 21 mutants of the GMP3 variety revealed that the relationship between mutants and controls was getting further. A six-character principal component analysis revealed that axis I's total variation accounted for 40.54 percent of the variation and had an eigenvalue of 2.43, whereas axis II's contribution to the variation was 19.02 percent and had an eigenvalue of 1.14. The findings indicate that stomata are excellent taxonomic evidence for identifying and analysing sugarcane varieties induced by colchicine-induced breeding.